2021
DOI: 10.1002/adom.202100550
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Fabrication of Resonator Waveguides Integrated Four‐Port Photonic Circuit from Flexible Organic Single Crystals

Abstract: By using a mechanophotonics approach, three flexible organic microcrystals of (E)‐1‐(4‐(dimethylamino)‐phenyl)iminomethyl‐2‐hydroxyl‐naphthalene (DPIN) are micromanipulated, and dual‐waveguides coupled ring resonator is fabricated. The flexibility of the DPIN crystal arises owing to its spring‐like expansion and contraction of π∙∙∙π stacked molecular chains along the (002) plane. The crystals also act as optical waveguides in straight and bent geometries with very low optical loss coefficients. The fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
69
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 36 publications
2
69
1
Order By: Relevance
“…The development of techniques for processing micrometersized molecular crystals is central to the realization of a miniature OPIC technology. However, the mechanophotonic [11][12][13][14][15][16] properties of flexible micro-sized crystals (<50 μm) on a substrate have not been explored well in the past due to the dearth of suitable techniques for crystal processing. Recently, atomic force microscopy (AFM), was suggested as an ideal technique for precise microcrystal processing.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The development of techniques for processing micrometersized molecular crystals is central to the realization of a miniature OPIC technology. However, the mechanophotonic [11][12][13][14][15][16] properties of flexible micro-sized crystals (<50 μm) on a substrate have not been explored well in the past due to the dearth of suitable techniques for crystal processing. Recently, atomic force microscopy (AFM), was suggested as an ideal technique for precise microcrystal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, atomic force microscopy (AFM), was suggested as an ideal technique for precise microcrystal processing. [11][12][13][14][15][16]20] These studies concluded that some of the drawbacks of silicon-based photonics could be potentially overcome by using suitable plastic crystals where the mechanical deformation does not alleviate the optical performance. The ease of fabrication by using this approach of OPICs with exceptional or strongly curved morphologies such as optical waveguides [11][12][13][14][15][16][20][21][22][23] bent at a right angle, or ring resonators or cavities [24] would allow for complete control over the light propagation in two dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations